(untitled) (Research, Society and Development, 2020)
The present article is part of a doctoral research under development in Graduate Program in Education in Science and Mathematics at the Federal University of Pará. One of the themes addressed is the teaching of Physics through the clay pans manufacturing process linking traditional with academic knowledge. The research has as empirical locus the traditional community Vila Que Era, located on the banks of the Caeté River in the rural area of the municipality of Bragança, state of Pará, Brazil. Among the objectives of the research, we intent to register the empirical knowledge of ceramic artisans on the production of ceramics and their main techniques. The chosen methodological procedure privileges ethnographic techniques, in order to facilitate the understanding of the relationship between Physics and the production of ceramics, especially pans, in the chosen community, seeking to establish ties that assist in the process of construction of the observed ethnophysical knowledge.